Reestablishing Indonesian Madhhab: ‘Urf and the Contribution of Intellectualism - Agus Moh Najib (Al-Jami'ah Research Centre, 2020)
The notion of Indonesian madhhab (school of Islamic law) is usually considered to have stopped with Hasbi and Hazairin. On the contrary, The notion of Indonesian madhhab has continued to grow and develop. Even though it has a variety of styles and trends, all of the notions of Indonesian madhhab have the same characteristics that are both contextual and formal. In addition to trying to formulate Islamic law in accordance with the context of Indonesian society, it also seeks to apply the results into statutory regulationswith formal applications. With such characteristics, the Indonesian madhhab places ‘urf (customs and community context) in a very important position as the main consideration in establishing Islamic law. Methodologically, to produce Islamic law in accordance with the Indonesian context, the Qur`anic text and the Hadith of the Prophet dialogue with Indonesian ‘urf. By using a historical approach to Islamic legal thinking, this article discusses the development of the ‘urf concept as put forward by the thinkers of Indonesian madhhab, since its emergence until now, and then discusses the influence of the notion of Indonesian madhhab regarding ‘urf in the legal products related to Islamic law in Indonesia. Following that scheme, this study found that the notion of Indonesian madhhab continues to develop along with the development of scholarly thinking about ‘urf from its thinkers.[Pemikiran tentang mazhab Indonesia biasanya dianggap telah berhenti sampai Hasbi dan Hazairin. Namun sebenarnya, pemikiran mazhab Indonesia tersebut terus mengalami perkembangan sampai dengan sekarang. Walaupun memiliki berbagai macam corak dan kecenderungan, namun semua pemikiran mazhab Indonesia tersebut memiliki karakteristik yang sama, yaitu bersifat kontekstual dan formal. Pemikiran mazhab Indonesia disamping berupaya memformulasikan hukum Islam sesuai dengan konteks masyarakat Indonesia, juga berusaha untuk menjadikan hasil formulasinya tersebut sebagai aturan perundang-undangan yang berlaku secara formal. Dengan karakteristiknya yang semacam itu, mazhab Indonesia menempatkan ‘urf (adat dan konteks masyarakat) pada posisi yang sangat penting sebagai dasar pertimbangan utama dalam penetapan hukum Islam. Secara metodologis, untuk menghasilkan hukum Islam yang sesuai dengan konteks Indonesia, dalam pemikiran mazhab Indonesia, teks Qur`an dan Hadis Nabi didialogkan dengan ‘urf Indonesia. Dengan menggunakan pendekatan sejarah terhadap pemikiran hukum Islam, artikel ini membahas perkembangan konsep ‘urf yang dikemukakan oleh para pemikir mazhab Indonesia, sejak mulai dicetuskannya hingga saat ini, kemudian dibahas juga pengaruh dari pemikiran mazhab Indonesia tentang ‘urf tersebut dalam produk aturan perundang-undangan yang terkait dengan hukum Islam di Indonesia. Dengan kajian tersebut, artikel ini menemukan bahwa pemikiran mazhab Indonesia terus berkembang seiring dengan perkembangan pemikiran tentang ‘urf dari para tokohnya.]